HUBUNGAN PEMANFAATAN SUMBER INFORMASI DENGAN SIKAP REMAJA TENTANG KESEHATAN REPRODUKSI DI SMA NEGERI 1 TOMPASO - Angely Belahdita Dayoh; Nancy Sylvia Bawiling; Jonesius Eden Manoppo (Yayasan Syalom Cipta Sumikolah, 2024)
Sources of information are media that play an important role for a person in determining attitudes and decisions to act. Sources of information can be obtained freely starting from peers, books, films, videos, and even easily opening sites via the internet. Reproductive health is a complete physical, mental and social condition, not only free from disease, disability in all aspects related to the reproductive system, its functions and processes. Many teenagers do not have sufficient information about health and also have wrong perceptions about reproductive health. Due to this lack of adequate understanding, many teenagers are not aware that they are carrying out activities that are risky for their reproductive health. This research aims to determine the relationship between the use of information sources and adolescents' attitudes about reproductive health at SMA Negeri 1 Tompaso. The research was conducted using quantitative methods with a cross-sectional approach and involved 76 respondents using the Proportionate Stratified Random Sampling technique and the data was analyzed using the chi-square test. The results of the research showed that some respondents, namely 46 respondents (60.5%), were in the category of lacking in the use of information sources and regarding the attitude of teenagers, 41 respondents (53.9%) were in the category of lacking. The results of the chi-square test show that there is a significant relationship between the use of information sources and attitudes (p-value 0.000 < 0.05). The conclusion from this research is that there is a relationship between the use of information sources and adolescents' attitudes about reproductive health.